The use of YouTube in Chemistry classes to motivate students. - López Guerrero, Gema; López-Guerrero, María del Mar (My University, 2023)
This communication describes an educational practice developed in the Chemistry subject, of the first year of the Degree in Electrical Engineering (University of Malaga, Spain). Based on the selection of a series of alternative methodologies to direct instruction, the students, through a prior inquiry process, have made, using the social network YouTube, an explanatory video of various points or important concepts included in the program of the subject. Based on the analysis of the videos (a total of 12), a questionnaire has been designed to determine the students' perceptions in relation to the tool and its educational implications, to which a total of 50 students responded. Based on the information collected, the students positively value the use of YouTube as a teaching resource, as well as the practice itself, highlighting a series of elements derived from the proposed teaching-learning process, such as creativity, fun and motivation in the acquisition of knowledge. Therefore, starting from the proposed research context, and taking into account its limitations, it can be determined that YouTube allows the development of communication skills, as well as the learning-to-learn competence, through autonomous, inquiring and experiential learning.
Keywords: Química - Estudio y enseñanza superior; Redes sociales en Internet; Chemistry; YouTube; Learning; Teaching; Engineering Degree